Implementasi Proses Pembuatan NIB dan Sertifikat Halal bagi UMKM Rujak Kikil Ibu Sulfailla - Syaifudin Ma’arif; Esti Maulida Apriliana; Chintia Sari; Nafia Ilhama Qurratu’aini (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This study explores the implementation of the process of obtaining the Business Identification Number (NIB) and halal certification for the Micro, Small, and Medium Enterprises (MSMEs) of Rujak Kikil Ibu Sulfaillah, serving as a case study in the culinary sector. The process of obtaining NIB and halal certification is crucial in ensuring compliance with prevailing regulations and standards, as well as unlocking opportunities for business development in an increasingly competitive market. Through a qualitative approach using direct observation and interviews, this study uncovers the challenges, obstacles, and impacts of the licensing and halal certification process on these MSMEs. Findings reveal that the slow licensing process can hinder business expansion, reduce competitiveness in the market, and limit access to certain market segments. Implications of these findings are discussed to identify necessary strategies to address these negative impacts and ensure the growth and sustainability of the business of Rujak Kikil Ibu Sulfaillah MSMEs.